2017
DOI: 10.1093/pubmed/fdx069
|View full text |Cite
|
Sign up to set email alerts
|

Examining the health status of homeless adults entering permanent supportive housing

Abstract: These findings suggest that access to housing will not easily remedy the well-documented premature mortality among chronically homeless adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 9 publications
2
41
0
Order By: Relevance
“…For example, research depicts the consistently high rates of acute infectious and parasitic diseases, diseases of the circulatory, respiratory and musculoskeletal system [ 13 ] as well as high rates of blood borne infections such as hepatitis C, HIV, tuberculosis, as well as myocardial infarction and pneumonia [ 14 16 ]. In addition to acute conditions, a high percentage of the homeless suffer from multimorbidity and chronic diseases [ 14 , 17 ] such as chronic pain [ 18 ] or chronic obstructive pulmonary disease [ 19 ]. A study by Queen, Lowrie, Richardson & Williamson [ 20 ] found in a homeless cohort with an average age of 42.8 years comparable levels of multimorbidity with those aged > 85 years in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…For example, research depicts the consistently high rates of acute infectious and parasitic diseases, diseases of the circulatory, respiratory and musculoskeletal system [ 13 ] as well as high rates of blood borne infections such as hepatitis C, HIV, tuberculosis, as well as myocardial infarction and pneumonia [ 14 16 ]. In addition to acute conditions, a high percentage of the homeless suffer from multimorbidity and chronic diseases [ 14 , 17 ] such as chronic pain [ 18 ] or chronic obstructive pulmonary disease [ 19 ]. A study by Queen, Lowrie, Richardson & Williamson [ 20 ] found in a homeless cohort with an average age of 42.8 years comparable levels of multimorbidity with those aged > 85 years in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…impairment of activities of daily living, or ADLs), frailty and persistent pain (Ivers, Cumming, Mitchell, & Peduto, ; Kojima, ; Leveille et al, ; Meijers et al, ; Pynoos, Steinman, & Nguyen, ; Rubenstein, ; Tinetti, Speechley, & Ginter, ). Individual fall risk factors may be even higher among formerly homeless adults living in PSH because of a growing practice known as vulnerability indexing, wherein homeless individuals with a higher risk of mortality due to medical conditions receive priority for placement in PSH (Henwood et al, ; Henwood, Lahey, Rhoades, Winetrobe, & Wenzel, ). PSH may also introduce a variety of environmental risk factors since the average age of the chronically homeless population was mid‐30s when the housing first approach was originally developed in the 1990s (Padgett, Henwood, & Tsemberis, ) and now is approaching 60 years old (Culhane et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The primary objective of the current study was to examine longitudinal change in insomnia as adults transition from homelessness to PSH, and whether additional factors may moderate the relationship between housing and insomnia for persons who have experienced homelessness. Specifically, we hypothesized that screening positive for insomnia would be mitigated upon entry to PSH, and that the relationship between housing status and insomnia would be moderated by mental health symptoms, physical health conditions (e.g., hypertension), and alcohol and tobacco consumption, all of which are experienced at disproportionately high rates among homeless and recently housed adults (6,10).…”
Section: Introductionmentioning
confidence: 99%